DAMPAK TATA KELOLA PERUSAHAAN TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN: ANALISIS SIMULASI KEBIJAKAN - Assrianti,; Bonar M. Sinaga,; Bayu Bandono, (Jurnal Aplikasi Bisnis dan Manajemen, 2021)
The concept of good corporate governance (GCG) has not been fully implemented by most business actors which is reflected in the assessment results of the ASEAN Corporate Governance Scorecard. The study aims to analyze the impact of external and internal factors including the implementation of GCG on the profitability and firm value in the LQ45 index of the Indonesia Stock Exchange. The econometric model is built as a system of simultaneous equations and estimated by using the Two-Stage Least Squares (2SLS) method and the impact simulation analysis policy. The result shows impact of decrease in gross domestic product is greater than increase in inflation. Furthermore if the decrease in gross domestic product or the increase in inflation that is resolved by company policies by improving corporate governance, making efficiency by reducing operational costs, and increasing total assets, have greater impact than the company resolved by improving corporate governance and making efficiency by reducing the cost of goods sold.Keywords: econometric model, external and internal factors, firm value, good corporate governance, profitability